2019
DOI: 10.1002/cam4.2229
|View full text |Cite
|
Sign up to set email alerts
|

Axl and autophagy LC3 expression in tumors is strongly associated with clinical prognosis of hepatocellular carcinoma patients after curative resection

Abstract: Background The role of Axl and LC3 as predictors of tumor recurrence and overall survival (OS) after hepatocellular carcinoma (HCC) resection remains unclear. Methods We retrospectively included 535 HCC patients who underwent hepatectomy from 2010 to 2014 in this study. Axl and the autophagy‐related marker LC3 were immunohistochemically assessed in tumors. Results Axl expression was significantly associated with advanced clinicopathological f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…Studies have shown that abberrant expression of Beclin-1 is strongly associated with the poor survival of various tumors such as intrahepatic cholangiocarcinoma ( 19 ), endometrial adenocarcinoma ( 20 ), colorectal cancer ( 21 ). LC3 was found to be related to tumor growth and progression of triple negative breast cancer ( 22 ), and be associated with clinical prognosis of pancreatic cancer ( 23 ), hepatocellular carcinoma ( 24 ) and colorectal cancer ( 25 ). Our study found that 127 and 131 ATGs were closely related to the OS of LGG patients from the TCGA and CGGA datasets, among which a total of 80 ATGs were present in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that abberrant expression of Beclin-1 is strongly associated with the poor survival of various tumors such as intrahepatic cholangiocarcinoma ( 19 ), endometrial adenocarcinoma ( 20 ), colorectal cancer ( 21 ). LC3 was found to be related to tumor growth and progression of triple negative breast cancer ( 22 ), and be associated with clinical prognosis of pancreatic cancer ( 23 ), hepatocellular carcinoma ( 24 ) and colorectal cancer ( 25 ). Our study found that 127 and 131 ATGs were closely related to the OS of LGG patients from the TCGA and CGGA datasets, among which a total of 80 ATGs were present in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the high LC3 expression, by immunohistochemistry analysis, both in the tumour and non-tumour liver was significantly associated with lower HCC recurrence in patients who underwent curative hepatectomy for HCC [ 60 ]. Therefore, LC3 was also considered a potential marker for predicting HCC recurrence and overall survival [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis involving 949 patients in HCC indicated that positive LC3 expression was related to the size of the tumor and the occurrence of HCC 45 . However, the combination of high Axl and low LC3 expression could significantly predict poorer prognosis for HCC patients who underwent hepatectomy in HCC 46 . Other data demonstrate that the complex involvement of TIPRL/LC3/CD133 in HCC aggressiveness can serve as potential biomarkers for early detection in a combined model or worked individually 47 .…”
Section: Autophagy and Autophagy-related Proteins In Hccmentioning
confidence: 97%